RESEARCH ON AESTHETIC COGNITION, FLOW EXPERIENCE AND TECHNOLOGY ACCEPTANCE IN VIRTUAL CULTURAL ACTIVITIES - Yen, Hui-Yun (PEOPLE: International Journal of Social Sciences, 2024)
This research explores the integration of aesthetic experience and technology acceptance in virtual cultural activities. Aimed at enhancing user engagement, the study utilizes a structured questionnaire to evaluate participants' aesthetic cognition, flow experiences, and technology acceptance. Methods include data collection from virtual cultural activities and subsequent analytical comparisons. Results indicate a preference for immersive and user-friendly technological interfaces, highlighting the significance of aesthetic cognition in cultural activities' success. The study suggests that improving interactive features could significantly enhance participation in virtual cultural settings.